2007
DOI: 10.1007/s00592-007-0250-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal-foetal status of copper, iron, molybdenum, selenium and zinc in obese gestational diabetic pregnancies

Abstract: Obesity is well known to be a contributory risk factor for several disease states, including diabetes mellitus. Paucity of data on maternal-foetal status of essential trace elements in obese diabetic pregnancies prompted us to undertake this study. Maternal venous and umbilical arterial and venous blood samples were collected from obese gestational diabetic patients (Body Mass Index (BMI) >30) and control obese pregnant women (BMI>30) at time of spontaneous delivery or caesarean sections and concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 27 publications
2
41
1
Order By: Relevance
“…In the present study, the correlation of essential and nonessential elements in scalp hair of DM-2 patients of both genders related to non-diabetic subjects belonging to Pakistan and Ireland was carried out. The results presented in Table 4 for healthy subjects and DM-2 patients confirm higher levels of Cd and Pb while lower values of Mg, Mn, Zn and Cr are associated with diabetes, which are consistent with other studies [31][32][33][34]. The results showed that the level of Mg was significantly lower in scalp hair samples of DM-2 patients as related to referents (P <0.001 ).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the correlation of essential and nonessential elements in scalp hair of DM-2 patients of both genders related to non-diabetic subjects belonging to Pakistan and Ireland was carried out. The results presented in Table 4 for healthy subjects and DM-2 patients confirm higher levels of Cd and Pb while lower values of Mg, Mn, Zn and Cr are associated with diabetes, which are consistent with other studies [31][32][33][34]. The results showed that the level of Mg was significantly lower in scalp hair samples of DM-2 patients as related to referents (P <0.001 ).…”
Section: Discussionsupporting
confidence: 89%
“…The characteristics of the studies included in the present meta-analysis are given in Table 1. Of the seven studies included in the meta-analysis, two were carried out in Kuwait [17, 20], one in China [16], one in Italy [18], one in Turkey [19], one in Hungar [22] and one in Sudan [21]. GDM was usually diagnosed during the 24–28 weeks of gestation.…”
Section: Resultsmentioning
confidence: 99%
“…The definition used for GDM was the criteria proposed by Carpenter and Coustan in three studies [18, 19, 21], and the World Health Organization (WHO) criteria in two studies [20, 22]. Blood samples for selenium measurement were collected in the second [16, 18, 19, 22] and third [16, 17, 20, 21] trimester of gestation. Six studies were case-control [1618, 2022], and one cross-sectional design [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations